1973
DOI: 10.1002/cber.19731060717
|View full text |Cite
|
Sign up to set email alerts
|

Heteroaromatische Komplexliganden. Die Kristallstruktur von Pentacarbonyl(2,4,6‐triphenyl‐phosphorin)chrom(0)

Abstract: Pentacarbonyl(2,4,6-triphenylphosphorin)chrom(O) kristallisiert monoklin in der Raumgruppe P21/c mit vier Molekiilen in der Elementarzelle. Die Pentacarbonylchromgruppe ist so an das Phosphoratom des Phosphorin-Ringes koordiniert, da8 die Cr -P-Bindung um 8" gegen die Ringebene geneigt ist. Die Cr-P-Bindung ist mit 2.37 8, relativ kurz. Der Phosphorin-King ist planar. Seine Geometrie stimmt weitgehend mit der P-unsubstituierter Phosphorine uberein. Heteroaromatic Complex LigandsThe Crystal Structure of Pentaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Due to the rather sterically demanding TMS group and the Br substituent both in α‐position of the phosphorus heterocycle, the planar aromatic ring is rotated out of the plane defined by three of the five carbonyl ligands and the phosphinine moiety (dihedral angle C(10)−W(1)−P(1)−C(5)=41.9°). A similar conformation has been observed for phosphinine complexes containing a Cr(CO) 5 or W(CO) 5 fragment …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the rather sterically demanding TMS group and the Br substituent both in α‐position of the phosphorus heterocycle, the planar aromatic ring is rotated out of the plane defined by three of the five carbonyl ligands and the phosphinine moiety (dihedral angle C(10)−W(1)−P(1)−C(5)=41.9°). A similar conformation has been observed for phosphinine complexes containing a Cr(CO) 5 or W(CO) 5 fragment …”
Section: Resultsmentioning
confidence: 99%
“…As imilar conformation has been observed for phosphininec omplexes containing aC r(CO) 5 or W(CO) 5 fragment. [17,18] The structuralc haracterizationo f20 nicely proves that the phosphinine 19 was regioselectivelyf ormed in af acile manner, (1) 1.213(11), C(1)ÀC(2) 1.451 (11), C(2)ÀC(3) 1.349 (10), C(3)ÀC(4) 1.415 (10), C(4)ÀC (5) 1.351(11), C(5)ÀO(1) 1.355(9), C(2)À Br(1)1.891 (7). www.chemeurj.org startingf rom 3-bromo-2-pyrone (16)a nd Me 3 Si-C P. This methodc an, thus, be used for the convenient synthesis of 6bromo-a nd 2-TMS-functionalized phosphinines and the overall reactionsequence is summarized in Scheme 8.…”
Section: Resultsmentioning
confidence: 99%
“…Since several complexes of phosphorins with transition metals have been described in the literature, but only two structural studies of such complexes are currently available (Vahrenkamp & N6th, 1972(Vahrenkamp & N6th, , 1973, we decided to undertake the determination of the crystal structure of the recently synthetized title compound (A) (Nief, Charrier, Mathey & Simalty, 1980). Compound (A) is also interesting because no structural data are available at the present time on sandwich complexes of Mn ~.…”
Section: Introductionmentioning
confidence: 99%
“…The first transition metal complexes containing phosphinine ligands were already described in the early 1970s by the groups of Nöth [10 -13], Fraser [14], Schmidbaur [15], and Dimroth [16]. Single-crystal X-ray diffraction studies performed by Vahrenkamp and Nöth for the metal carbonyl complexes [Cr(κP-C 5 H 2 P-2,4,6-Ph 3 )(CO) 5 ] [11] and [Cr(η 6 -C 5 H 2 P-2,4,6-Ph 3 )(CO) 3 ] [12] revealed that phosphinines can coordinate via their P lone pair and also via their π system. Homologous molybdenum and tungsten pentacarbonyl complexes were structurally characterised by the groups of Ashe [17] and Mathey [18].…”
Section: Introductionmentioning
confidence: 99%